Interactions of Fluorinated Surfactants with Diphtheria Toxin T-Domain: Testing New Media for Studies of Membrane Proteins - Rodnin, Mykola V. (The Biophysical Society, 2008)
The principal difficulty in experimental exploration of the folding and stability of membrane proteins (MPs) is their aggregation outside of the native environment of the lipid bilayer. To circumvent this problem, we recently applied fluorinated nondetergent surfactants that act as chemical chaperones. The ideal chaperone surfactant would 1), maintain the MP in solution; 2), minimally perturb the MP's structure; 3), dissociate from the MP during membrane insertion; and 4), not partition into the lipid bilayer. Here, we compare how surfactants with hemifluorinated (HFTAC) and completely fluorinated (FTAC) hydrophobic chains of different length compare to this ideal. Using fluorescence correlation spectroscopy of dye-labeled FTAC and HFTAC, we demonstrate that neither type of surfactant will bind lipid vesicles. Thus, unlike detergents, fluorinated surfactants do not compromise vesicle integrity even at concentrations far in excess of their critical micelle concentration. We examined the interaction of surfactants with a model MP, DTT, using a variety of spectroscopic techniques. Site-selective labeling of DTT with fluorescent dyes indicates that the surfactants do not interact with DTT uniformly, instead concentrating in the most hydrophobic patches. Circular dichroism measurements suggest that the presence of surfactants does not alter the structure of DTT. However, the cooperativity of the thermal unfolding transition is reduced by the presence of surfactants, especially above the critical micelle concentration (a feature of regular detergents, too). The linear dependence of DTT's enthalpy of unfolding on the surfactant concentration is encouraging for future application of (H)FTACs to determine the stability of the membrane-competent conformations of other MPs. The observed reduction in the efficiency of Förster resonance energy transfer between donor-labeled (H)FTACs and acceptor-labeled DTT upon addition of lipid vesicles indicates that the protein sheds the layer of surfactant during its bilayer insertion. We discuss the advantages of fluorinated surfactants over other types of solubilizing agents, with a specific emphasis on their possible applications in thermodynamic measurements.